AMR surveillance in Canada: Insights from the 2025 Priority Pathogen List - Kahina Abdesselam; Pia K. Muchaal; Aanchal Mishra; Raymond-Jonas Ngendabanka; Kanchana Amaratunga; Sakhi Mittal; Wallis Rudnick; Anna-Louise Crago; Robyn Mitchell; Stephanie Alexandre; Tanya Lary (PLoS ONE, 2026)
Background Antimicrobial resistance (AMR) remains a growing threat to public health and healthcare systems. In 2015, Canada published its first AMR Priority Pathogen List. In 2025, an updated list was developed to reflect evolving resistance trends, emerging pathogens, and advances in national surveillance capacity. Objective To conduct a qualitative analysis of the 2025 AMR prioritization results to evaluate the strengths and limitations of current Canadian AMR surveillance systems in detecting and monitoring high-risk pathogens. Methodology As described in a companion paper, 29 AMR pathogens were prioritized using a multi-criteria decision analysis (MCDA) framework, informed by Canadian data from 2017 to 2022. Pathogens were assessed across nine weighted criteria, including incidence, treatability, and a newly integrated health equity dimension. Criteria weights were derived from expert consensus, and sensitivity analyses confirmed ranking stability. This paper presents a qualitative analysis examining how well these pathogens are captured by existing national surveillance systems and highlights data integration gaps. Results The 2025 prioritization identified significant shifts in Canada’s AMR landscape, including the emergence of Candida auris , drug-resistant Neisseria gonorrhoeae , and Mycoplasma genitalium as high-priority threats. Canada’s approach aligns closely with international frameworks (e.g., WHO, CDC), enhancing its global relevance. AMRNet, a national laboratory-based AMR surveillance platform, has the capacity to eventually capture 90% of prioritized pathogens, and over half of pathogens are currently covered by enhanced national systems that integrate laboratory and epidemiologic data. A quadrant-based assessment revealed strong coverage for several pathogens, but persistent gaps remain, particularly for those lacking routine diagnostics. Over one-third of prioritized pathogens disproportionately affect marginalized populations, underscoring the importance of integrating disaggregated sociodemographic data into surveillance. Conclusion Canada has made meaningful progress toward integrated, equity-informed AMR surveillance. Continued investment and collaboration are essential to close persistent data gaps, improve responsiveness, and support targeted public health action .